Creativity and inspiration woven technique by using excessive plastic bag / Azni Hanim Hamzah...[et.al] - Hamzah, Azni Hanim; Abdui Manan, Salina; Ismail, Noor Hafiza; Mat Yusuf, Nurhikma; Ab Aziz, Nurul Izza (2016)
Creativity is understood as processes or methods of increasing the flow of valuable ideas. Designers are familiar with group and individual processes. In this research is more in application woven technique by reused plastic bag. Focusing on application three-type -weaving techniques such as frame loom, crochet and plaiting techniques. This idea examines the possibilities of waste plastic bags to produces product by explores the three-type plastic bags material, High-density polyethylene (HDPE), Low density polyethylene (LDPE) and Polypropylene (PP). Beside that, it one way to be creative by using excessive plastic bags. However, to solve a problem of excessive plastic bags that can course pollution and encourage people to recycle plastic bags. The design from the weaving technique gives a different impact for ordinary products such as shoes, table cover and wall piece. By reuse the waste plastic bag material it was not just help our environment but it give an idea and encourage public to be creative by using wastage in our surrounding.